Business Investment Decision (BID) Tool for strengthening seed business - Jayanth, R.; Rajendran, S. (2024)
The seed sector is critical to agricultural productivity, yet entrepreneurs in this space face significant challenges, including limited financial management skills, operational inefficiencies, financial constraints, and lack of market reach. These issues are compounded by the reliance on ad-hoc, manual processes for decision-making. To address these challenges, this report introduces the Business Investment Decision (BID) tool, a comprehensive digital platform designed to empower seed-sector entrepreneurs and businesses. The BID tool offers structured formats for financial planning, investment analysis, and business growth, enabling users to make informed decisions. Currently available in Excel and web-based formats, with plans for a desktop version, the tool includes modules for business background, business environment, financial management, budgeting, valuation, risk management, and more. Its target users include small and medium enterprises (SMEs) in the seed sector, as well as businesses in other industries at various stages of development. The tool has been validated through applications in diverse settings, including RTB EAGEL in Nairobi and Potato ARC Technology in India. Potential benefits of the BID tool include simplified business planning, ease of use for beginners, the ability to raise funds, and enhanced strategic decision-making. Future development plans include expanding the web version, integrating artificial intelligence for industry comparisons and strategy formulation, incorporating real-time data, and enabling seamless integration with accounting systems. Keywords Business Investment Decision (BID) tool, financial management, decision-making frameworks, business growth, investment analysis, digital platform, operational efficiency, financial planning, budgeting, risk management.